Idiopathic paroxysmal myoglobinuria - Özsoylu, Şinasi; Akgün, Suat (The Turkish Journal of Pediatrics, 1966)
A case of idiopathic paroxysmal myoglobinuria is reported. The first attack was observed at nine years of age following physical activity. Its diagnosis was made with Blondheim et al's method and confirmed by spectroscopic and electrophoretic studies. With starch gel electrophoresis, three benzidine positive bands were demonstrated in the urine of this patient. Haptoglobin was present in the serum, and muscle glycogen and phosphorylase activity could not be determined.